Merekabentuk kerangka proses pengubahsuaian rumah berdasarkan kepada penilaian kondisi bangunan di Kota Samarahan, Sarawak - Mohd. Amran, Hasbullah (2018)
This exploratory study is aimed to investigate prima facie that there are many crack lines of post-modification house structure elements due to lack of sensitivity and unskilled practitioners in aspects of home renovation in Kota Samarahan District, Sarawak. A total of 67 respondents were randomly selected in this field study. Five major factors have affected the post-modification house defect is the neglect of the requirements of the house structure plan, construction period, soil compaction, maintenance and full involvement of the project manager during the renovation process. A study was done based on visual assessment using Building Defects Index (BC!) and Building Condition Assessment (BCA) to assess 642 physical disability cases. A total of 382 cracked structures on the structure and walls of brick houses were evaluated using non-destructive testing methods. Ultrasonic Pulse Velocity and Rebound Hammer has been used to identify the current performance of structural elements. The result shows that the average crack size is 0.5785 which is a good value under British Standard 1881. Immediate recovery or replacement measures need to be made on six critical home units, repairs should be done at 25 units of medium scale and only routine monitoring measures are needed to ensure that defects are not easy to spread to the rest of the units. The results of this study have found that when the crack width of the structure exceeds 2.0 mm then the performance of the concrete strength decreases <20 MPa and the value of PV <3.0 km I s would be in critical condition. Studies show that the post-modification home is a moderate performance of its solidarity, meaning that a framework for the renovation process needs to be established. This study suggests that, the public must also be exposed to the forensic knowledge of the building and the authorities should be firm in enforcing existing regulations.